Paciente de sexo femenino de 38 años con litiasis renal y sobrepeso. - Gavilanes Amaiquema, Kelly Nahomy (2021)
The present clinical case corresponds to the study of a 38-year-old patient who attended a medical consultation due to a clinical picture of 5 days of evolution characterized by Odinodinea plus Odynophagia. He also refers 10/10 lumbar pain, more accentuated in recent days, he refers to having a personal pathological history of hepatic steatosis, family pathological history, father's kidney failure, he does not smoke or drink alcohol. It is diagnosed by imaging, left renal lithiasis. The objective of the study is to improve your nutritional condition. The nutritional assessment was carried out through: anthropometric assessment, biochemical assessment, food consumption, clinical signs. In the anthropometric evaluation we have a weight of 59 kg and a height of 150 cm, which shows us that the patient is in a nutritional state of overweight according to the WHO with a BMI of 26 kg / m2. Regarding the biochemical assessment, anemia according to Hemoglobin of 11.4 g / dl, Hematocrit of 37%, there is evidence of alteration in the lipid profile with high values, cholesterolemia according to cholesterol 246.57 mg / dl and hypertriglyceridemia according to triglycerides 160 mg / dl, excessive food consumption and sedentary lifestyle.